Efektivitas Penyampaian Informasi Petugas Avsec Mengatasi Konflik Komunikasi dengan Penumpang Mengenai Kapasitas Powerbank Bandar Udara Adi Soemarmo - Fatchul, Raden; Frida, Tamara (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The delivery of information carried out by aviation security officers to passengers in conveying information in the form of provisions in carrying electronic devices in the form of power banks is a communication that must be carried out firmly but still in a sympathetic manner. In a domestic flight, the carrying of power bank electronic devices is very strictly regulated in a regulation in the form of Circular Letter Number 15 of 2018 concerning the provisions of carrying portable battery chargers (power banks) and spare lithium batteries on aircraft. The purpose of this study is to determine and explain the effectiveness of information delivery by aviation security officers in overcoming communication conflicts with passengers regarding power bank capacity at Adi Soemarmo Boyolali International Airport. This research is a quantitative study using data collection methods using questionnaires with the population being passengers who carry power banks with capacities exceeding the applicable regulations. The results of this study are with the value of tcount (10,657) ˃ ttable (1,1991) then there is an influence on how to deliver information carried out by aviation security officers in overcoming communication conflicts with passenge rs, besides the influence of the delivery of information carried out by aviation security officers in overcoming communication conflicts with passengers is 59.3%, the remaining 40.7% is influenced by other factors outside this study.